2016
DOI: 10.1021/acs.macromol.6b01814
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Free Perpendicular Diblock Copolymer Films: The Synergy Effect of Surface Topography and Chemistry

Abstract: We propose a direct self-assembly mechanism towards obtaining defect-free perpendicular lamellar phases of diblock copolymer (BCP) thin films. In our numerical study, a thin BCP film having a flat top surface is casted on a uni-directional corrugated solid substrate. The substrate is treated chemically and has a weak preference toward one of the two BCP components. Employing self-consistent field theory (SCFT), we find that there is an enhanced synergy between two substrate characteristics: its topography (geo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
4
18
0
Order By: Relevance
“…The C 1 is more stable for large u values. Similar effects of u were reported by Man et al 29,30 They showed that increasing u can cause a phase transition from perpendicular to parallel orientation of lamellar phases. This indeed indicates that for both cylinder and lamellae, the substrate preference u can cause a phase transition from perpendicular to parallel orientation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The C 1 is more stable for large u values. Similar effects of u were reported by Man et al 29,30 They showed that increasing u can cause a phase transition from perpendicular to parallel orientation of lamellar phases. This indeed indicates that for both cylinder and lamellae, the substrate preference u can cause a phase transition from perpendicular to parallel orientation.…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with the results shown in Figure 4, and also with previous studies. 21,29,30 B. The unidirectional substrate corrugation along the b-direction…”
Section: A the Unidirectional Substrate Corrugation Along The A-direc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar orthogonal guidance has been reported from a corrugated surface formed from an underlying BCP, , shallow trenches, or steps or facets in the substrate surface, , comprising topographic modulations with comparable feature size to the BCP. An incommensurate domain spacing between the upper and lower layers is required to avoid alignment of the upper microdomains parallel to those in the lower layer. …”
Section: Resultsmentioning
confidence: 99%
“…In order to facilitate the fabrication of defect-free films, further treatments are needed. As examples to techniques that have been developed to tailor the self-assembly behavior of BCP thin films we mentioned electric field alignment 4,5 , shear alignment 6,7 , microwave annealing 8 , and thermal annealing 1,2,[9][10][11][12][13][14][15][16] . Besides these approaches, solvent vapor annealing (SVA) 1,3,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] has been used to enhance the mobility of polymer chains, and to facilitate the annihilation of defects.…”
Section: Introductionmentioning
confidence: 99%